Biosynthesis of Rhamnolipid Biosurfactant by Newly Isolated Marine Bacterium Methylobacterium mesophilicum MTCC 6839 from Oil Contaminated Sites at Alang Coast, Gujarat, India - Vyas, T. K.; Dave, B. P. (International Journal of Bio-resource and Stress Management, 2023)
Oil spillage into marine environment either from seeps or from anthropogenic sources, is subject to pose a major environmental pollution. Alang coast (21° 21´ N, 72° 12´ E), 60 km from Bhavnagar, Gujarat, India, is known for its extensive shipbreaking activities. These activities release tonnes of oil into the marine environment, polluting the marine ecosystem and thus, threatening biological diversity. Methylobacterim mesophilicum MTCC 6839, a potential marine crude oil degrader was isolated from Alang Coast. In the present study, M. mesophilicum has been evaluated for physiological changes during oil biodegradation. Cells produced biosurfactant, an amphiphilc molecule and thus increased emulsification activity of oil. It produced rhamnolipid biosurfactant as analyzed by thin layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR). It has been also examined for surface hydrophobicity and emulsification activity as a function of biosurfactant production. Results indicate that cells altered their cells surface hydrophobicity when grown on a hydrophobic carbon source. Also, an increasing in biosurfactant production led to increase in cell surface-hydrophobcity and emulsification activity. The results thus, indicate the potential role of cell surface hydrophobicity and emulsification activity in response to biosurfactant production by marine M. mesophilicum in remediation of crude oil contaminated sites. Biosurfactant production is significantly correlated with degradation and emulsification activity at 0.001 level whereas, with growth at 0.01 level. Thus, isolated MTCC 6839 can be used for bioremediation of oil contaminated marine sites.